2003
DOI: 10.1046/j.1365-2222.2003.01721.x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary adenylate cyclase‐activating polypeptide, effects in the human nose

Abstract: These results imply that PACAP is an important endogenous mediator in human upper airways, with a potential role as a regulator of vascular smooth muscle, secretion, plasma extravasation, neutrophil recruitment and cytokine activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…In rodents, PACAP causes relaxation of tracheal smooth muscles (Araki and Takagi, 1992;Conroy et al, 1995;Foda et al, 1995;Hiramatsu et al, 1995;Yoshihara et al, 1997;Berisha et al, 2002;Lindén et al, 2003), promotes bronchodilation (Lindén et al, 1995(Lindén et al, , 1999 and increases nasal airway resistance (Kinhult et al, 2003). The relaxant effect of PACAP on the trachea is mediated through activation of the cAMP/ PKA-dependent (Araki and Takagi, 1992;Kanemura et al, 1993;Foda et al, 1995), NO/cGMP-dependent (Saotome et al, 1998), and carbon monoxide-dependent transduction pathways (Kinhult et al, 2001a).…”
Section: Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 99%
“…In rodents, PACAP causes relaxation of tracheal smooth muscles (Araki and Takagi, 1992;Conroy et al, 1995;Foda et al, 1995;Hiramatsu et al, 1995;Yoshihara et al, 1997;Berisha et al, 2002;Lindén et al, 2003), promotes bronchodilation (Lindén et al, 1995(Lindén et al, , 1999 and increases nasal airway resistance (Kinhult et al, 2003). The relaxant effect of PACAP on the trachea is mediated through activation of the cAMP/ PKA-dependent (Araki and Takagi, 1992;Kanemura et al, 1993;Foda et al, 1995), NO/cGMP-dependent (Saotome et al, 1998), and carbon monoxide-dependent transduction pathways (Kinhult et al, 2001a).…”
Section: Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 99%
“…A clinical study involving intranasally administered PACAP demonstrated a potential role for PACAP as a regulator of vascular smooth muscle, secretion, plasma extravasation, neutrophil recruitment, and cytokine activity (73). However, to date, no clinical trials have been performed on investigating the effects of intranasal PACAP on memory or cognition.…”
Section: Pituitary Adenylate Cyclase Activating Polypeptidementioning
confidence: 99%
“…PACAP, enhanced the plasma leakage effect of bradykinin, and in 1997 Cardell et al [24] showed that PACAP-38 stimulation of rat skin caused plasma leakage and suggested that it could be due to histamine release. More recent studies showed that in the human nose PACAP-38 increased albumin concentration in nasal secretion fluid, which is a sign of plasma leakage [25]. The selective inhibitor used in our study, a 44-amino acid mutant of the 61-amino acid peptide maxadilan, had minor inflammatory effects (plasma leakage) when applied for 10 min at concentrations 100 times exceeding that of maxadilan.…”
Section: Discussionmentioning
confidence: 57%
“…Studies of the biological effects of PACAP revealed that it enhanced the permeability-inducing effects of bradykinin in the skin of rabbits [22, 23] and rats [24]. Further, in the human nose, PACAP-38 caused extravasation of plasma albumin [25]. It may thus be expected that PACAP and maxadilan could have the same effects in the hamster cheek pouch (HCP), a skin-like tissue without glands and hair follicles.…”
Section: Introductionmentioning
confidence: 99%